Influence of Temporary Employment on Employee Performance: A Case Study of Safaricom Limited - Ruth Moraa Ongera; Dennis juma (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Despite a growing acceptance that temporary employment is likely to be a persisting and significant feature of contemporary work, there is no clear idea about how it affects the satisfaction, well being and performance of workers. Studies attempting to shade some light on the influence of temporary employment on employee performance are more generalistic and have failed to give detailed insights and analysis of the issues under the current study especially in Kenya. The purpose of the study therefore was to examine the influence of temporary employment on employee performance at Safaricom Limited. The study adopted a descriptive design. Descriptive statistics such as mean and percentages were applied in the data analysis. The study found out that there was a positive relationship between temporary employment and employee performance. Employees took up temporary employment as an alternative to lack of permanent employment, and with the hope of gaining permanent employment in the longer term.